Organisational Readiness for Open Government Data-Driven Co-Creation - Vujković, Petra; Jukić, Tina; Vrbek, Sanja (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Open government data (OGD) is widely promoted for transparency and innovation, yet reuse remains uneven. Co-creation offers a route to public value by enabling public organisations and external stakeholders to jointly design or improve services and policies using open data. This paper synthesises what the OGD-driven co-creation literature says about internal organisational conditions that support effective participation. We conducted a systematic literature review of English-language studies indexed in the Web of Science database. The analysis focuses on organisational factors, understood as both drivers and barriers, within public organisations rather than ecosystem-level conditions. The findings indicate that readiness depends on more than data release: it also requires strategic commitment to openness, clear procedures and incentives, a learning-oriented culture, leadership that enables cross-boundary collaboration, staff competences in data and participatory methods, and the ability to assure data quality. We discuss implications for strengthening organisational capacities for sustained, data-enabled co-creation and identify priorities for further empirical research.